2015
DOI: 10.1016/j.celrep.2015.02.028
|View full text |Cite
|
Sign up to set email alerts
|

FBH1 Catalyzes Regression of Stalled Replication Forks

Abstract: DNA replication fork perturbation is a major challenge to the maintenance of genome integrity. It has been suggested that processing of stalled forks might involve fork regression, in which the fork reverses and the two nascent DNA strands anneal. Here, we show that FBH1 catalyzes regression of a model replication fork in vitro and promotes fork regression in vivo in response to replication perturbation. Cells respond to fork stalling by activating checkpoint responses requiring signaling through stress-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 33 publications
1
83
0
Order By: Relevance
“…A particularly attractive possibility is that fork reversal might occur and/or persist as a consequence of Dna2 helicase dysfunction. The resulting chicken-foot structure, which effectively contains a single-ended DNA double-strand break at the tip of the regressed DNA branch, could account for DNA damage checkpoint activation51, which we observe in Dna2 helicase-defective cells (Figs 2d and 5c). A four-way chicken-foot DNA intermediate would also be amenable to resolution by Yen1; perhaps more so than by Mus81-Mms4, which is greatly stimulated by pre-existing nicks within DNA junctions, such as those that may be present in HR-dependent joint molecules and maturing HJs prior to a final ligation step293043.…”
Section: Discussionmentioning
confidence: 72%
“…A particularly attractive possibility is that fork reversal might occur and/or persist as a consequence of Dna2 helicase dysfunction. The resulting chicken-foot structure, which effectively contains a single-ended DNA double-strand break at the tip of the regressed DNA branch, could account for DNA damage checkpoint activation51, which we observe in Dna2 helicase-defective cells (Figs 2d and 5c). A four-way chicken-foot DNA intermediate would also be amenable to resolution by Yen1; perhaps more so than by Mus81-Mms4, which is greatly stimulated by pre-existing nicks within DNA junctions, such as those that may be present in HR-dependent joint molecules and maturing HJs prior to a final ligation step293043.…”
Section: Discussionmentioning
confidence: 72%
“…A recent report has also suggested that a very early ATM activation event in response to replication stress -the sensing of regressed replication forks -is triggered by the FBH1 (encoded by FBXO18) helicase (Fugger et al, 2015). After its activation, ATM induces a wide spectrum of signal transduction pathways that connect processes involved in DNA repair, cell metabolism, bioenergetics, as well as protein translation and transcription.…”
Section: Cellular Effects Of Atm Signalingmentioning
confidence: 99%
“…In vitro studies of fork remodeling require modifications to the DNA such as mismatches at the fork junction to prevent spontaneous branch migration. Even with these modifications, there are many enzymes that can catalyze fork regression of naked DNA substrates including BLM, WRN, HLTF, FANCM, FBH1, ZRANB3, and SMARCAL1 [6069]. …”
Section: How Does the Replication Checkpoint Prevent Fork Collapse?mentioning
confidence: 99%
“…New genetic evidence suggests that the homologous recombination protein RAD51 is essential for fork regression [79], and the FBH1 helicase also plays a role [69]. Another enzyme, RECQ1 participates in restoring replication forks that form due to low dose CPT treatment [80].…”
Section: How Does the Replication Checkpoint Prevent Fork Collapse?mentioning
confidence: 99%